2016
DOI: 10.15255/cabeq.2015.2207
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Inhibition Processes in a Hollow-fiber Membrane Bioreactor for Hybridoma Culture. Development of a Mathematical Model

Abstract: The performance of a hollow-fiber membrane bioreactor (HFBR) (molecular weight cut-off 30 kD, fiber surface area 2050 cm 2 ) containing a culture of hybridoma cells has been investigated. Experimental data were used as basis to develop a model of general application. Concentrations of fundamental nutrients (glucose and glutamine), inhibitory products (ammonium and lactate), and monoclonal antibodies (MAb) against bovine lactoferrin (IgG 1 ) were monitored over time. Exchange of nutrients and products occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…However, Macias et al by employing a semi-empirical approach, found that intermediate molecular weight toxins are primarily removed by diffusive transport [ 28 ]. Legazpi et al developed a mathematical model based on experimental data to assess the mass transfer efficiency of hollow fiber membranes, and the solute concentration distribution in the hollow fiber membrane module was in good agreement with experimental findings [ 29 ]. It should be pointed out that the mathematical model in Legazpi et al only considered diffusive solute transport [ 29 ].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, Macias et al by employing a semi-empirical approach, found that intermediate molecular weight toxins are primarily removed by diffusive transport [ 28 ]. Legazpi et al developed a mathematical model based on experimental data to assess the mass transfer efficiency of hollow fiber membranes, and the solute concentration distribution in the hollow fiber membrane module was in good agreement with experimental findings [ 29 ]. It should be pointed out that the mathematical model in Legazpi et al only considered diffusive solute transport [ 29 ].…”
Section: Introductionmentioning
confidence: 73%
“…Legazpi et al developed a mathematical model based on experimental data to assess the mass transfer efficiency of hollow fiber membranes, and the solute concentration distribution in the hollow fiber membrane module was in good agreement with experimental findings [ 29 ]. It should be pointed out that the mathematical model in Legazpi et al only considered diffusive solute transport [ 29 ]. Sorrell et al developed a mathematical model for the mass transfer behavior of an artificial liver hollow fiber membrane module, focusing on the transport of acetaminophen hepatotoxin and oxygen in the hollow fiber tubes, and their model assumed that the solute transport in the tube-side region is convective and diffusive, while only diffusive transport occurs in the regions of both hollow fiber membranes and shell-side [ 30 ].…”
Section: Introductionmentioning
confidence: 73%
“…Legazpi et al used a hollow fiber bioreactor that consisted of a bundle of 2565 cellulose fibers with a molecular weight cut-off value of 30 kD and a length of 13 cm. The results showed that the concentration of monoclonal antibody produced by the hollow fiber bioreactor (HFBR) was high and the time was short, but the consumption of the medium for producing monoclonal antibody (MAb) per milligram was higher (Table 3) [68,69]. The hollow fiber bioreactor is also a promising tool to expand the production of stem cells to provide enough cells [70].…”
Section: Other Applicationsmentioning
confidence: 99%
“…MAb production data employing different culture techniques[68]. Data were reported by Legazpi, reprinted with permission from Ref [69]…”
mentioning
confidence: 99%